How Time Budget Pressure, Competence, and Independence Affect Audit Quality Through Professional Skepticism ? - Diana, Nur; Maslichah, Maslichah; Adhikara, MF. Arrozi; F, Dewi Diah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research uses the sustained time restriction as a tool for professional skepticism and looks at how auditor independence and competence affect auditing. SEM AMOS analysis and a survey of 113 auditors in Malang Raya revealed that autonomous work and auditor competence had a substantial influence on skepticism. Better auditing was accomplished, nevertheless. The continuum between competent performance and audit quality is preserved by professional skepticism. The quality and skepticism of audits are not significantly impacted by time constraints. The findings imply that extrinsic limitations like time limits are less significant than the auditor's inner qualities, such as competence, proficiency, and skepticism. The investigation of audit practice illumination, auditor skepticism clarification, and profitability skepticism is still on going.